Development of the DIY (Do-It-Yourself) Learning Model to Improve Problem-Solving Skills of Children Aged 5–6 Years - Utami Purbasari; Debie Susanti; Nita Priyanti (Kirana Publisher (KNPub), 2026)
Problem-solving skills are essential competencies that need to be developed during early childhood education. However, learning practices in many early childhood institutions are still teacher-centered, limiting children's opportunities to explore and solve problems independently. This study aimed to develop and examine the effectiveness of a DIY (Do-It-Yourself) learning model to improve problem-solving skills among children aged 5–6 years. The research employed a Research and Development (R&D) approach adapted from the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The effectiveness of the model was tested using a pre-experimental design with a one-group pretest–posttest approach. The research participants consisted of 14 children from Group B at TK Negeri Parakanlima, Purwakarta. Data were collected using observation sheets measuring four indicators of problem-solving ability. The results showed a significant improvement in children's problem-solving skills, with the average score increasing from 52.43 in the pretest (developing category) to 80.36 in the posttest (very well-developed category). The N-Gain value of 0.65 indicated a moderate-to-high effectiveness level. The findings demonstrate that the DIY learning model can provide meaningful learning experiences through hands-on construction activities using recycled materials, encouraging children's independence, creativity, and critical thinking. Therefore, the DIY learning model can serve as an innovative pedagogical alternative to support the development of problem-solving skills in early childhood education.